Increased Strength following Achilles Tendon Rupture Repair is Associated with Return to Same Level of Play in Patients with Higher Pre-Injury Level of Activity. Issue 4 (22nd October 2020) - Holzgrefe, Russell E.; McCarthy, Timothy; Wilson, Jacob M.; Bariteau, Jason T.; Labib, Sameh A.
Category: Hindfoot; Sports; Trauma Introduction/Purpose: Rupture of the Achilles tendon is a common injury that requires a lengthy duration of recovery and rehabilitation. Patients of various levels of physical activity, ranging from professional high-impact sports to low-impact recreational activities, can be affected by this injury. Often, one of the most important outcomes from the patient's perspective is the ability to return to the same pre-injury level of sporting activity after recovery. The objective of the current study is to examine the relationship between global ankle strength and the ability to return to previous level of play following surgical repair of an Achilles tendon tear. Methods: Patients aged 18-50 years old at a minimum 1-year post-op from surgical repair of an isolated Achilles tendon rupture were recruited to return for a study visit. Patients reported both pre-injury and current activity level using the 10-point Tegner Activity Level Scale. Isokinetic strength testing was performed and the Isokinetic Strength Score (ISS) was calculated using maximal effort dorsiflexion and plantarflexion strength at 30o/s, 90o/s, and 240o/s comparing the operative and uninvolved extremity. The primary outcome was the patients' ability to return to same level of play or within 1 Tegner activity level. Logitistic regression analysis was used to determine the relationship between ISS and return to play. Subgroup analysis was performed on patients participating in high level athletic activity (pre-injury Tegner >= 7) an those participating in only recreational or low level activity (pre-injury Tegner <7). Results: A total of 36 patients (mean 35 years, 72% male) completed the study protocol at a mean 1.8 years post-op (range 1 year to 3.6 years). Logistic regression revealed no association between ISS and return to play in the complete cohort. Subgroup analysis revealed that for 20 patients who had participated in high level competitive athletics prior to injury (Pre-injury Tegner >= 7), for every 16 point increase in ISS, the odds ratio for return to same level of play was 8.3 (p=0.055) and the OR for return to within 1 Tegner level of play was 6.3 (p=0.043). There was no association between ISS and return to previous activity in the 16 patients with lower pre-injury levels of activity. Conclusion: Improved ankle strength was associated with return to previous level of activity only in patients who participate in high level athletic activity. These results suggest that patients with more strenuous athletic activity prior to injury are more dependent on recovery of ankle strength in the post-operative time period in order to return to their previous high level of play. In contrast, regaining strength may be less important for returning to normal activities for less active patients.